Maternal Reproductive Health Indicators and Their Correlation with Low Birth Weight: Evidence from a Community-Based Cohort at Pasean-Pamekasan Health Center - Badrus, Arkha Rosyaria; Khairoh, Mifftahul; Purwitasari, Alief Ayu; Fathiyyah, Nurul; Mulyadi, Jesica (Jambura Medical and Health Science Journal, 2026)
Introduction: Low birth weight (LBW) is a major cause of neonatal morbidity and mortality in developing countries. This study analyzed the relationship between maternal reproductive health indicators and LBW incidence at the Pasean Health Center, Pamekasan.Method: A prospective cohort study was conducted on 72 third-trimester pregnant women followed until delivery. Data on maternal age, interpregnancy interval, nutritional status, and antenatal care (ANC) visits were obtained through interviews and anthropometric measurements. Infant birth weight was measured within 24 hours postpartum. Logistic regression analysis was used with a 5% significance level.Results: The prevalence of LBW was 15.3%. Maternal age 20 years significantly increased the risk of LBW (AOR=2.45; 95% CI: 1.18–5.07; P=0.016), while short interpregnancy interval (24 months) also showed a significant effect (AOR=1.87; 95% CI: 1.02–3.45; P=0.042). Poor maternal nutritional status emerged as the strongest predictor (AOR=3.12; 95% CI: 1.58–6.15; P=0.001).Conclusion: These results highlight the importance of improving maternal nutrition, ensuring adequate birth spacing, and delaying early pregnancies. Strengthening primary health care interventions focusing on preconception and antenatal nutrition is essential to reduce LBW and improve neonatal health outcomes. Keywords: Antenatal care, low birth weight, maternal nutrition, pregnancy interval, reproductive health